(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article explores the significant role of technology in teaching English to technical college students. Technological tools, including multimedia resources, language learning apps, online platforms, and interactive software, have transformed the traditional English classroom. The paper examines the benefits and challenges of integrating technology, including increased student engagement, access to authentic materials, personalized learning, and improved communication skills. Practical strategies for using technology effectively are discussed, such as blended learning, flipped classrooms, and collaborative online projects. The study concludes that when used properly, technology enhances language learning, motivates students, and prepares them for academic and professional success.